Numerical investigation on the phase change process of different shaped macro encapsulated PCM - R. Patel, Jay; K. Rathod, Manish (International Journal of Engineering and Technology, 2018)
Latent heat energy storage using macro encapsulated phase change material is an emerging technique for thermal energy storage applica- tions. The main aim of the present investigation is to investigate the melting process of phase change material filled in different shaped configurations. The selected different cavities are square, circular and triangular. A mathematical model based on convection dominated melting is required to be developed, especially in view of the complex flow geometries encountered in such problems. Thus, an attempt has been made to develop a model using ANSYS Fluent 16.2 to investigate the heat transfer rate and solid-liquid interface visualization of PCM filled in different shapes of cavity. It is found that triangular shaped macro encapsulated PCM melts faster than square and circu- lar shaped encapsulated PCM.Â Â Â